Viruses as potential nanomachines - Jokanović Vukoman; Živković Marija; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2021)
In this paper viruses are considered as very efficient nano-machines that produce numerous copies of them. Observing these nano-architectures, the question arises: which molecular forces and processes make up the set of such structures, given that they are extremely inspiring for development of new technologies at the nano level. There is a need for deep understanding of individual molecular building blocks and their structures, properties of their assemblies and dynamic behavior.